Discursos de clase en el ciclo salitrero: la construcción ideológica del sujeto obrero en Chile, 1890-1912 - Pinto Vallejos, Julio (Revista de Historia Social y de las Mentalidades, 2025)
Within the time-frame which saw the emergence of a modern working-class identity among Chile’s popular sectors, this article explores the «class dis-courses» that circulated in the nitrate-producing regions at the turnof the 20thcentury. Its argument suggests that these discourses fed into the making of a new collective self-image in which workers came to see themselves primor-dially as members of a collective body defined by its relationship to the labor process, thatis, as a class. From this perception emerged demands for human recognition, citizenship and revolutionary change which inspired most work-ing-class projects during the 20thcentury.
Keywords: Collective Identities; Working Class; Nitrate History